Social networks as a means for HIV prevention. A systematic review - Ortiz-Rodríguez, Blanca (Revista Española de Comunicación en Salud, 2020)
Introduction: In 2018 there were a total of 141,552 new cases of HIV diagnosed in 50 countries. The urgent need to reduce HIV in the population has been a driving force in developing innovative internet-based research. Social networks have proven to be effective and acceptable for health promotion activities. Objectives: To synthesize the available evidence about the usefulness of social networks as a means to carry out health promotion interventions to prevent HIV in young population. Methodology: Systematic review of scientific articles. A research was done with the databases: Pubmed, Web of Science, Scopus, Cinahl, Cochrane and PsyInfo. In addition, we consulted the journals AIDS Edudation and Prevention and AIDS & Behaviour, and a review of the bibliography of articles. The sample included people between 15 and 39 years with negative or unknown HIV status. Results: Seven articles met the inclusion criteria. Positive results were found regarding behavioural changes, knowledge acquisition, participation and acceptability of the intervention. Conclusion: Social networks have proven to be a useful means of carrying out health promotion interventions to prevent HIV in young population.